ESTIMASI SEKUESTRASI KARBON PADA TANAMAN POKOK HUTAN PRODUKSI DI KABUPATEN TUBAN, JAWA TIMUR - Dhina Mustikaningrum; Anisa Rosida (Jurnal Tanah dan Sumberdaya Lahan, 2023)
Tuban Regency feels the impact of climate change on various economic supporting sectors. This makes the adaptation efforts in these sectors important as well as climate change mitigation to support the reduction of greenhouse gas emissions, one of which is by maintaining the existence of production forests. This study aims to identify the amount of carbon uptake by the two main plants. The method used is tree diameter data collection without harvesting. The diameter data is used to calculate biomass and carbon sequestration with allometric equations. The results showed that teak had the lowest biomass value produced at the age of 5 years at 94.26 t ha-1, and the highest biomass was recorded at the age of 10 years at 200.33 t ha-1. Meanwhile, mahogany at the age of 5 years, 10 years and 15 years had a total biomass of 40.76 t ha-1, 53.55 t ha-1 and 146.37 t ha-1, respectively. From the biomass value, the total carbon stored in teak aged 5 years, 10 years and 15 years, respectively, was 43.36 t ha-1, 92.15 t ha-1 and 90.05 t ha-1. While the the total carbon stores in mahogany aged 5 years, 10 years and 15 years respectively was 18.75 t ha-1, 24.63 t ha-1 and 67.33  t ha-1. The teak and mahogany production forests in this age group have a total area of ​​more than 280 ha, so that the total carbon sequestration at BKPH Sundulan is 78,471 tons C from teak production forests and 1,835.3 tons C absorbed from mahogany production forests.